2022
DOI: 10.9734/ijpss/2022/v34i2331605
|View full text |Cite
|
Sign up to set email alerts
|

Character Association and Path Coefficient Analysis in Upland Rice (Oryza sativa L.) for Grain Yield and Quality Characters

Abstract: The present investigation was undertaken to evaluate Twenty Five Upland Rice genotypes. There are various aspects to move up rice yield, such as creating of irrigation work, development of rice ecosystems, soil conditions, traditional practices, and breeding of high yielding genotypes. Among them, it seems that the most effective and economic way available is to develop different rice ecosystems especially Upland Rice Genotypes. High to moderate phenotypic and genotypic coefficient of variation were observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Panicle length has a significant (P ≤ 0.05) positive correlation with grain yield per hectare and a highly significant (P ≤ 0.01) positive correlation with grains per panicle, panicle density, and grain weight per clump, with the same findings also reported by Riyanto et al (2012) and Rajasekhar et al (2022) in their studies on characteristic association and path coefficient analysis in upland rice (Oryza sativa L.) for grain yield and quality traits. The number of grains per panicle The results also indicated that panicle density had a significant (P ≤ 0.05) positive correlation with the percentage of filled grain and a substantial (P ≤ 0.01) positive relationship with the panicle length, number of grains per panicle, grain weight per clump, and grain yield per hectare.…”
Section: Correlation Among Production Parameterssupporting
confidence: 84%
“…Panicle length has a significant (P ≤ 0.05) positive correlation with grain yield per hectare and a highly significant (P ≤ 0.01) positive correlation with grains per panicle, panicle density, and grain weight per clump, with the same findings also reported by Riyanto et al (2012) and Rajasekhar et al (2022) in their studies on characteristic association and path coefficient analysis in upland rice (Oryza sativa L.) for grain yield and quality traits. The number of grains per panicle The results also indicated that panicle density had a significant (P ≤ 0.05) positive correlation with the percentage of filled grain and a substantial (P ≤ 0.01) positive relationship with the panicle length, number of grains per panicle, grain weight per clump, and grain yield per hectare.…”
Section: Correlation Among Production Parameterssupporting
confidence: 84%